Sudden Unexpected Death Of Infancy: The Value Of Postmortem Microbiological Sampling - Tan Choo Xiang; Nadia Anuar; Norazlah Bahari; Nur Syahrina Rahim (Malaysian Society of Pathologists, 2024)
Introduction: Sudden unexpected death of infancy (SUDI) refers to when the occurrence of death is sudden and not expected in previously healthy child. Infection is recognized as one of the leading identifiable causes of SUDI, and a significant proportion of currently unexplained infant deaths may be infection related, possibly mediated by abnormal systemic immune responses. We would like to share some of these cases and highlight the importance of microbiological investigations as part of investigations of SUDI. Case Reports: Case 1: A 2-month-old female, was found unresponsive on bed by the mother. Autopsy tissue histopathological examination showed acute stress changes in thymus and features of early pneumonic changes. Microbiology investigations isolated pure cultures of E. coli from blood, lungs and spleen tissue cultures. Case 2: A 2-monthold female, was found unresponsive by the father. There were history of vomiting and shortness of breath post-feeding the day before. Postmortem investigations concluded Klebsiella pneumoniae infection as primary cause of death. Additionally, there were features to suggest misalignment of pulmonary vein with pulmonary hypertension, enlarged heart with pleural effusions and chronic stress changes in thymus. Case 3: A 3-month-old female, with 2-week history of NICU admission after birth following meconium aspiration syndrome, was found unresponsive by the caretaker. Autopsy findings revealed lung changes in keeping with previous pneumonitis and Group B streptococcal sepsis. Learning Points: The postmortem microbiological investigations remain a critical value in investigations of SUDI. Moreover, these microbiological investigations will identify unexpected infections in cases with absence of histologically identifiable focus of infection. Appropriate and correct technique of postmortem microbiology sampling will increase the likelihood in identifying infection-related cause.